2011
DOI: 10.1371/journal.pone.0014671
|View full text |Cite
|
Sign up to set email alerts
|

The Vasoactive Potential of Kisspeptin-10 in the Peripheral Vasculature

Abstract: Splice products of the Kiss1 protein (kisspeptins) have been shown to be involved in a diverse range of functions, including puberty, metastasis and vasoconstriction in large human arteries. Circulating Kisspeptin-10 (Kp-10) plasma levels are low in normal individuals but are elevated during various disease states as well as pregnancy. Here, we investigated the potential of Kp-10, the shortest biologically active kisspeptin, to influence microvascular effects, concentrating on the cutaneous vasculature. Kp-10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 39 publications
2
30
1
Order By: Relevance
“…Both KP and its receptor GPR54 were detected in HUVECs (Figure 2A). The previous [15,20] and present studies suggest that endothelial cells may serve as an alternative source of KP and, thereby, act in a local paracrine/autocrine fashion. The levels of KISS1 mRNA transcripts were significantly enhanced in the HUVECs cultured under the mimicked ischaemic conditions compared with those cultured under the normal conditions ( Figure 2B; P < 0.05).…”
Section: Kp and Gpr54 In Huvecssupporting
confidence: 68%
“…Both KP and its receptor GPR54 were detected in HUVECs (Figure 2A). The previous [15,20] and present studies suggest that endothelial cells may serve as an alternative source of KP and, thereby, act in a local paracrine/autocrine fashion. The levels of KISS1 mRNA transcripts were significantly enhanced in the HUVECs cultured under the mimicked ischaemic conditions compared with those cultured under the normal conditions ( Figure 2B; P < 0.05).…”
Section: Kp and Gpr54 In Huvecssupporting
confidence: 68%
“…However, to date mRNA studies of kisspeptin receptor distribution in whole heart samples have reported low but varying mRNA expression by northern blot [2], expression was not detected by PCR [3], [4], [32] except by Sawyer and colleagues, who were also able to detect mRNA encoding murine kisspeptin, albeit at very low copy number [46]. We now report for the first time, the expression of kisspeptin and the kisspeptin receptor protein in human, rat and mouse heart, and have shown that kisspeptins are potent positive inotropes in in vitro cardiac preparations from these species.…”
Section: Discussionmentioning
confidence: 99%
“…Mice at 13 weeks of age were infused for 4 weeks with KP‐10 and/or P234, a GPR54 antagonist (Peptide Institute, Osaka, Japan), using osmotic minipumps (Model 1002; Alzet; DURECT Corporation, Cupertino, CA). The time course and dose of KP‐10 and P234 infusion were decided on the basis of others’ previous and our preliminary data …”
Section: Methodsmentioning
confidence: 99%